MANAJEMEN KOMUNIKASI LINTAS BUDAYA DALAM PELAYANAN KEIMIGRASIAN : PENGALAMAN WNA CHINA DI INDONESIA: CROSS-CULTURAL COMMUNICATION MANAGEMENT IN IMMIGRATION SERVICES: THE EXPERIENCE OF CHINESE CITIZENS IN INDONESIA - Wili Pratama; Virra Wirdhingsih; Hanifa Maulidia (Polteknik Imigrasi, 2025)
Globalization has intensified cross-cultural interactions, particularly in public service sectors such as immigration. Indonesia, as a destination country for international mobility, has recorded a significant increase in the arrival of Chinese foreigner, reaching 131,155 individuals by March 2025, with 83,079 visas issued. This situation requires immigration services that are not only accurate and timely but also culturally sensitive. This study aims to examine the role of cross-cultural communication management in enhancing the effectiveness of immigration services for Mandarin-speaking communities. Using a qualitative-descriptive approach and literature review, this article analyzes key cultural dimensions such as social hierarchy, collectivism, and long-term orientation common within Chinese society and how these factors influence communication patterns and service expectations during visa application processes. The findings reveal that failure to accommodate cultural differences may lead to dissatisfaction, while appropriate communicative adaptation fosters greater trust and satisfaction with immigration institutions. Therefore, understanding and applying principles of cross-cultural communication is a crucial strategy in delivering inclusive and professional immigration services.